2017
DOI: 10.5603/oj.2017.0003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of lens extraction for intraocular pressure reduction in eyes with primary angle closure glaucoma and primary angle closure

Abstract: introduCtion. The purpose of the study was to evaluate the intraocular pressure (IOP) lowering effect of lens removal in eyes with primary angle closure glaucoma (PACG) and primary angle closure (PAC). MATERIALS AND METHODS. This study was a retrospective analysis of 114 eyes of 97 patients (83 women, 14 men; mean age 69.9 years) with PACG and PAC treated with lens extraction. Outcome measures: age, gender, visual acuity, IOP reduction over time, preoperative and postoperative number of IOP-lowering medication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In the present study, we have shown for the first time that LE in PAC patients, with IOP of up to 30 mm Hg, can change the clinical and anatomic parameters of the eye in a way that brings them closer to the age norm. In addition, unlike other studies in the same field, 18,37 we have analyzed the results of LE in patients of a wider age range (from 41 y) and without prior LPI. 38 However, it should be noted that, compared with preoperative parameters, which were not statistically different between the groups with different treatments (Tables 3 and 4), after the intervention (LE and LPI), both groups approached the control, but to a different extent (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have shown for the first time that LE in PAC patients, with IOP of up to 30 mm Hg, can change the clinical and anatomic parameters of the eye in a way that brings them closer to the age norm. In addition, unlike other studies in the same field, 18,37 we have analyzed the results of LE in patients of a wider age range (from 41 y) and without prior LPI. 38 However, it should be noted that, compared with preoperative parameters, which were not statistically different between the groups with different treatments (Tables 3 and 4), after the intervention (LE and LPI), both groups approached the control, but to a different extent (Fig.…”
Section: Discussionmentioning
confidence: 99%